Handbook of human factors and ergonomics - Salvendy, Gavriel, 1938-; Karwowski, Waldemar, 1953- (Wiley, 2021)
"In the newly revised Fifth Edition of Handbook of Human Factors and Ergonomics, Drs. Gavriel Salvendy and Waldemar Karwowski deliver a comprehensive exploration of workplace environment design, human-machine interfaces, and cutting-edge research on the reduction of health and safety risks. The editors have compiled practical material from an international team of leading experts in ergonomics and human factors that will benefit specialists in the area, as well as safety engineers and human-computer interaction specialists.The Handbook includes information culled from over 7500 sources and features brand new coverage in areas like artificial intelligence, social media, information technology and cybersecurity, and data analytics. Numerous case studies demonstrate the real-world application of the concepts and methods discussed within and showcase the extraordinary developments in the field since the publication of the Fourth Edition in 2012."-- Provided by publisher.
Keywords: Human engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books